DINAMIKA SANTRI-ABANGAN DI BALIK EKSISTENSI MASJID LAWEYAN, SURAKARTA - Zaenal Abidin Eko Putro (Harmoni, 2015)
Many scholars carry out studies on the existence of Santri and Abangan in Java. Various books and journals discuss those studies but they just emphasize on debate between Islam and its local context. This paper aims to describe the relationship between Santri and Abangan that can build a tolerance in certain area in Java. This study employs qualitative approach and the data is collected through observation, document, and interview to some Muslims in Laweyan Mosque, Surakarta. The study shows that Abangan and Santri do not have restriction. This condition can hamper the development of Islamic radicalism in this ancient mosque.